Classroom Challenges in Developing an Intercultural Early Learning Program for Refugee Children - Dachyshyn, Darcey; Kirova, Anna (Alberta Journal of Educational Research, 2011)
The project described here was aimed at piloting an intercultural, multilingual, early learning program that was genuinely responsive to the circumstances and early learning needs of preschool refugee children and parents from three ethnocultural communities—Somali, Sudanese, and Kurdish—in a large city in Western Canada. We discuss the unique challenges faced by the classroom team consisting of a first-language facilitator for each of the three languages spoken by the children in the classroom and an English-speaking teacher. Because of the lack of sufficient time to consult families and communities about their cultural practices and expectations for young children before the beginning of the program, these challenges included setting up the classroom environments and routines, managing the four languages, negotiating the emerging curriculum content, and learning to work as a team in a multi-sectoral project. Cet article décrit un projet visant le pilotage d’un programme d’apprentissage interculturel et plurilingue pour jeunes enfants qui s’est avéré authentiquement adapté aux circonstances et aux besoins en apprentissage d’enfants réfugiés d’âge préscolaire et de leurs parents originaires de trois communautés ethnoculturelles – somalienne, soudanaise et kurde – dans une grande ville dans l’Ouest du Canada. Nous discutons des défis particuliers qu’affronte l’équipe pédagogique consistant en un moniteur de langue première pour chacune des trois langues parlées par les enfants dans la classe et un enseignant de langue anglaise. N’ayant pas eu le temps de consulter les familles et les communautés avant le début du programme au sujet de leurs pratiques culturelles et de leurs attentes par rapport aux jeunes enfants, nous avons dû, entre autres défis, établir le milieu et les routines de la salle de classe, gérer les quatre langues, négocier le contenu du nouveau programme d’études et apprendre à travailler en équipe dans le cadre d’un projet multisectoriel.